Microscopic spread of low rectal cancer in regions of mesorectum: Pathologic assessment with whole-mount sections - Wang, Zhao (World J Gastroenterol, 2004)
AIM: To assess the microscopic spread of low rectal cancer in mesorectum regions to provide pathological evidence for the necessity of total mesorectal excision (TME). METHODS: A total of 62 patients with low rectal cancer underwent low anterior resection and TME, surgical specimens were sliced transversely on the serial embedded blocks at 2.5 mm interval, and stained with hematoxylin and eosin (HE). The mesorectum on whole-mount sections was divided into three regions: outer region of mesorectum (ORM), middle region of mesorectum (MRM) and inner region of mesorectum (IRM). Microscopic metastatic foci were investigated microscopically on the sections for the metastatic mesorectal regions, frequency, types, involvement of lymphatic vessels and correlation with the original rectal cancer. RESULTS: Microscopic spread of the tumor in mesorectum and ORM was observed in 38.7% (24/62) and 25.8% (16/62) of the patients, respectively. Circumferential resection margin (CRM) with involvement of microscopic metastatic foci occurred in 6.5% (4/62) of the patients, and distal mesorectum (DMR) involved was 6.5% (4/62) with the spread extent within 3 cm of low board of the main lesions. Most (20/24) of the patients with microscopic metastasis in mesorectum were in Dukes C stage. CONCLUSION: Results of the present study support that complete excision of the mesorectum without destruction of the ORM is essential for surgical management of low rectal cancer, an optimal DMR clearance resection margin should be no less than 4 cm, further pathologic assessment of the regions in extramesorectum in the pelvis is needed.